Pengenalan Deep Learning Bagi Guru Sekolah Menengah Kejuruan dalam Peningkatkan Literasi Teknologi Pendidikan - M Bambang Purwanto; Despita Despita; Mietha Nella; Dita Marisa; Rohmial Rohmial (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This community service activity aims to increase educational technology literacy among Vocational High School (SMK) teachers by introducing the basic concept of Deep Learning and its application in the world of education. This training was motivated by the urgent need to equip educators with basic understanding and skills regarding artificial intelligence (AI), especially Deep Learning, to be able to keep up with rapid technological developments and relevant to vocational education. Through practice-based training using simple tools such as Teachable Machine, teachers are given hands-on experience in creating simple machine learning models that are applicable in the school environment. The results of the pre-test and post-test showed a significant increase in understanding in the participants. The group discussions also produced various ideas for the application of AI such as a face-based attendance system, student voice recognition, and recommendations for learning materials according to students' interests. Despite challenges such as limited infrastructure and teacher learning time, this activity proves that a practical and contextual training approach can increase teachers' motivation to integrate technology into learning. Similar training is highly recommended to be replicated in other schools to support equitable access to modern educational technology.